2016
DOI: 10.1515/znc-2016-0162
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of micropollutant naproxen with a selected fungal strain and identification of metabolites

Abstract: Pharmaceuticals are widely used for treating human and animal diseases. Naproxen [(S) 6-methoxy-α-methyl-2-naphthalene acetic acid] and its sodium salt are members of the α-arylpropionic acid group of nonsteroidal anti-inflammatory drugs. Due to excessive usage of naproxen, this drug has been determined even in drinking water. In this study, four fungal strains Phanerochaete chrysosporium, Funalia trogii, Aspergillus niger, and Yarrowia lipolytica were investigated in terms of naproxen removal abilities. Accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…This result indicated that metabolite formed by loss of methyl group (O-desmethylnaproxen, C 13 H 12 O 3 ). Besides LC/MS analysis we used 1 HNMR, and 13 CNMR analysis in our former study to identify this metabolite [14].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This result indicated that metabolite formed by loss of methyl group (O-desmethylnaproxen, C 13 H 12 O 3 ). Besides LC/MS analysis we used 1 HNMR, and 13 CNMR analysis in our former study to identify this metabolite [14].…”
Section: Resultsmentioning
confidence: 99%
“…As described before, in our group's previous study O-desmethylnaproxen was obtained by Aspergillus niger spore suspension and identified by proton nuclear magnetic resonance ( 1 H NMR) and carbon-13 nuclear magnetic resonance ( 13 C NMR) [14].…”
Section: O-desmethylnaproxen Production and Isolationmentioning
confidence: 93%
See 1 more Smart Citation
“…Some species of Penicillium can be used effectively in TCS, NP and hormones degradation [198][199][200][201][202]. The yeast Yarrowia lipolytica has been studied for the expression of cytochrome P450 and it seems capable of degrading diclofenac and NPX [191,203]. Trichoderma harzianum is able to degrade 17 β-estradiol [204] and CBZ with a performance similar to that of Pleurotus ostreatus [205].…”
Section: Mycoremediationmentioning
confidence: 99%
“…For this reason, an alternative might be the enzymatic oxidation. It was observed that the selected fungal strains can effectively degrade selected pharmaceuticals (Aracagök et al 2018). Fungal enzymes also appear to be particularly promising in this issue, for example heme-thiolate peroxidase, which is unspecific peroxygenase extracted from the Black poplar mushroom Agrocybe aegerita (AaeUPO EC 1.11.2.1) discovered over decade ago (Ullrich 2004).…”
Section: Introductionmentioning
confidence: 99%